Antioxidant Activity of Kawista Leaves and Fruit Skin Extract (Limonia acidissima L) from Karawang Regency - Rahmi, Hayatul; Rahmadewi, Reni (Jurnal Midpro, 2020)
Antioxidants are compounds that can capture free radical activity because they can donate one electron to free radicals. The purpose of this study was to determine how much the antioxidant activity of leaf extract and kawista fruit skin from Karawang Regency. This research is an experimental, the research method used extraction (maceration) with cold aquades, hot aquades, and ethanol 96%. Tested of antioxidant activity can be done by measuring DPPH radical breakfast (1,1-diphenyl-2-picrylhydrazyl) using a UV-Vis spectrophotometer. The results were obtained by the highest antioxidant activity of kawista leaf extract with hot water solvents : 134.56 ppm and the highest antioxidant activity in kawista fruit skin samples achieved by ethanol solvents with a value of 381.36 ppm.